2019
DOI: 10.1101/563007
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transposon-insertion sequencing screens unveil requirements for EHEC growth and intestinal colonization

Abstract: 31 Enterohemorrhagic Escherichia coli O157:H7 (EHEC) is an important food-borne 32 pathogen that colonizes the colon. Transposon-insertion sequencing (TIS) was used to 33 identify genes required for EHEC and commensal E. coli K-12 growth in vitro and for 34 EHEC growth in vivo in the infant rabbit colon. Surprisingly, many conserved loci 35 contribute to EHEC's but not to K-12's growth in vitro, suggesting that gene acquisition 36 during EHEC evolution has heightened the pathogen's reliance on certain metaboli… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 120 publications
0
19
0
Order By: Relevance
“…We attempted to use transposon-insertion sequencing (TIS) to identify genetic loci contributing to S. flexneri colonization and pathogenesis, as we have done with V. cholerae (53, 54), V. parahaemolyticus (55), and EHEC (56). Initially, a high-density transposon mutant library in S. flexneri was created using a mariner -based transposon that inserts at TA dinucleotide sites in the genome.…”
Section: Resultsmentioning
confidence: 99%
“…We attempted to use transposon-insertion sequencing (TIS) to identify genetic loci contributing to S. flexneri colonization and pathogenesis, as we have done with V. cholerae (53, 54), V. parahaemolyticus (55), and EHEC (56). Initially, a high-density transposon mutant library in S. flexneri was created using a mariner -based transposon that inserts at TA dinucleotide sites in the genome.…”
Section: Resultsmentioning
confidence: 99%
“…For example, high-resolution transcriptomics, transposon mutagenesis, and Grad-seq data exist for Streptococcus pneumoniae (Aprianto et al, 2016(Aprianto et al, , 2018Hor et al, 2020;Rowe et al, 2019;van Opijnen and Camilli, 2012;Warrier et al, 2018). More generally, various transposonsequencing approaches have been applied to bacterial pathogens under virulence conditions (Karlinsey et al, 2019;Rendón et al, 2020;Warr et al, 2019), and dual RNAseq has become the gold-standard to chart the transcriptional landscape of pathogens during infection (Montoya et al, 2019;Pisu et al, 2020;Ritchie and Evans, 2019;Westermann et al, 2017). Re-inspection of these data may provide invaluable information on potentially new biological roles carried out by small proteins in bacterial pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…CvpA bears structural similarity to the inner membrane mechanosensitive ion channels MscS and MscL (HHPred, Phyre2) (22), and whole-proteome localization analysis in E. coli assigned CvpA to the inner membrane (32). Furthermore, several protein modeling algorithms (PSLPred, HHPred, Phobius, Phyre2, OCTOPUS) (22) predict that CvpA is a 4-pass inner membrane protein with a periplasmic C-terminus ( Fig 1A). To experimentally verify these assignments, we generated two plasmids that inducibly express sfGFP-CvpA fusions, with sfGFP on either the N-or C-terminus, enabling visualization of the localization of CvpA in EHEC.…”
Section: Cvpa Localizes To the Ehec Cell Peripherymentioning
confidence: 99%
“…The gene cvpA was identified in screens for genes required for intestinal colonization in several enteric pathogens, including Vibrio cholerae, Vibrio parahaemolyticus, and Salmonella Typhimurium (19)(20)(21), but the mechanism(s) that account for the colonization defects have not been characterized. We recently found that CvpA is required for the foodborne intestinal pathogen enterohemorrhagic Escherichia coli O157:H7 (EHEC) to optimally colonize the colon of infant rabbits; moreover, EHEC cvpA deletion mutants were highly sensitive to bile, and in particular the bile salt deoxycholate (DOC) (22). EHEC causes hemorrhagic colitis and in some cases the severe complication hemolytic uremic syndrome, a condition in which damage to blood vessels of the kidney microvasculature leads to renal failure.…”
Section: Introductionmentioning
confidence: 99%